Large Two‐Photon Absorption of Terpyridine‐Based Quadrupolar Derivatives: Towards their Applications in Optical Limiting and Biological Imaging. Issue 3 (28th December 2012) - He, Tingchao; Lim, Zheng Bang; Ma, Lin; Li, Hairong; Rajwar, Deepa; Ying, Yongjun; Di, Ziyun; Grimsdale, Andrew C.; Sun, Handong
Abstract Developing organic chromophores with large two‐photon absorption (TPA) in both organic solvents and aqueous media is crucial owing to their applications in solid‐state photonic devices and biological imaging. Herein, a series of novel terpyridine‐based quadrupolar derivatives have been synthesized. The influences of electron‐donating group, type of conjugated bridge, as well as solvent polarity on the molecular TPA properties have been investigated in detail. In contrast to the case in organic solvents, bis(thienyl)‐benzothiadiazole as a rigid conjugated bridge will completely quench molecular two‐photon emission in aqueous media. However, the combination of alkylcarbazole as the donor and bis(styryl)benzene as a conjugation bridge can enlarge molecular TPA cross‐sections in both organic solvent and aqueous media. The reasonable two‐photon emission brightness for the organic nanoparticles of chromophores 3–5 in the aqueous media, prepared by the reprecipitation method, enables them to be used as probes for in vivo biological imaging.